The SMOOTH-Robot: A Modular, Interactive Service Robot - Krüger, Norbert; Fischer, Kerstin; Manoonpong, Poramate; Palinko, Oskar; Bodenhagen, Leon; Baumann, Timo; Kjærum, Jens; Rano, Ignacio; Naik, Lakshadeep; Juel, William Kristian; Haarslev, Frederik; Ignasov, Jevgeni; et al. (Frontiers in Robotics and AI, 2021)
The SMOOTH–robot is a mobile robot that – due to its modularity – combines a relatively low price with the possibility to be utilized for a large variety of tasks in a wide range of domains. In this paper, we demonstrate the potential of the SMOOTH–robot through three use cases, two of them being performed in elderly care homes. The robot is designed such that it can either make itself ready (or can quickly be changed by staff) to perform different tasks. We carefully considered important design parameters such as the appearance, intended as well as unintended interactions with users and the technical complexity, such that the acceptability of the robot, as well as a sufficient degree of utilization, is achievable. Three demonstrated use cases indicate that such robots could contribute to an improved work environment, have the potential to free resources of care staff which could be allocated to actual care-giving tasks. Moreover, the SMOOTH-robot can be used in many other domains as we will also exemplify in this paper.